2017
DOI: 10.1021/acsnano.7b00497
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Size and Shape on the Anatomical Distribution of Endotoxin-Free Gold Nanoparticles

Abstract: The transport and the delivery of drugs through nanocarriers is a great challenge of pharmacology. Since the production of liposomes to reduce the toxicity of doxorubicin in patients, a plethora of nanomaterials have been produced and characterized. Although it is widely known that elementary properties of nanomaterials influence their in vivo kinetics, such interaction is often poorly investigated in many preclinical studies. The present study aims to evaluate the actual effect of size and shape on the biodis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 55 publications
7
115
0
Order By: Relevance
“…Although often assumed spherical, nanoparticles feature a large variety of geometric and irregular shapes . Particles with equal composition and similar dimensions might present drastically different behaviors as a consequence of their shape, such as surface‐binding capability, cellular uptake and release, optical and plasmonic effects, to name some of the major properties affected by particle morphology.…”
Section: Nanoparticle Parametersmentioning
confidence: 99%
“…Although often assumed spherical, nanoparticles feature a large variety of geometric and irregular shapes . Particles with equal composition and similar dimensions might present drastically different behaviors as a consequence of their shape, such as surface‐binding capability, cellular uptake and release, optical and plasmonic effects, to name some of the major properties affected by particle morphology.…”
Section: Nanoparticle Parametersmentioning
confidence: 99%
“…The dependence of cellular uptake, biodistribution, and clearance rate on NP size has been widely investigated by many groups. 111-115 To date, several types of CAs have been developed for various applications in MRI, which can be classified according to their chemical composition (Gd-, Mn-, Fe-, Dy- or Ho-based CAs; Table 2). A deep understanding of the involved mechanisms between size effect and proton relaxation will undoubtedly benefit the rational design of T 1 or T 2 CAs for high-performance MRI.…”
Section: Factors Influencing Relaxivity Of Mri Contrast Agentsmentioning
confidence: 99%
“…They found that all types of NPs induced complement activation (through measurements of C3bc, C3a, C5a, and sC5b-9) within the first 5 minutes of contact with blood, but rods and disks generate more profound complement activation than spheres at later timepoints [40]. Recently, Bigini et al demonstrated that spherical and star-like Au NPs show the same percentage of accumulation but a different localization in liver, and only star-like Au NPs could be able to accumulate in lung [41]. …”
Section: Physicochemical Properties Of Nanoparticles Modulate Innamentioning
confidence: 99%